Synthesis of Cyclic and Heterocyclic Compounds via Gold-Catalyzed Reactions - Wang, Qiang; Shi, Min (Synlett, 2017)
This account outlines the latest advances from our group in the field of gold catalysis. A variety of cyclic and heterocyclic compounds, containing different sized skeletons, are synthesized selectively by fine-tuning the substrates, catalysts, and ligands. Au(I)/Au(III) redox catalysis is applied in our latest work through adding external oxidation. The reaction mechanisms are discussed in detail. Moreover, the photoredox catalytic process is also introduced briefly, which opens avenues for the development of new strategies in gold chemistry.1 Introduction2 Gold-Catalyzed Cycloisomerization of Enynes3 Gold-Catalyzed Intramolecular Cyclization of Propargylic Ester Substrates4 Gold-Catalyzed C(sp3)–H Functionalizations5 The Au(I)/Au(III) Redox Catalytic Cycle6 Conclusion
Keywords: gold catalysis; cycloisomerization; propargylic esters; Au(I)/Au(III) redox catalysis